Interactive Sport Court Lines using LED for Efficient Space Management - Nathan, Shelena Soosay; Mazlan, Muhammad Arif Aiman; Kamarulzaman, Siti Hajar Munirah; Saahari, Intan Nur Fatiha (Multidisciplinary Applied Research and Innovation, 2022)
Sport activity has become a norm in our daily life because of the importance of sport that benefits our health. The current traditional sports culture halls have various flaws, resulting in waste of space resources. People just play specific different sports everyday which results in a huge waste of space. This study provides a solution which is to develop a Design of Interactive Court Lines for Sports using LED’s using Arduino that reacts to the selected choice and generates the desired court’s line. This project is targeted for kids, adults and citizens of all kinds or groups of people. The study uses the Input Process Output (IPO) method which acts as a guideline throughout the development of this project. There are several hardware components that were used in developing this project which are Arduino UNO, P10 LED, HC-05 Bluetooth module, DMD Connecter, Jumper wires for building the prototype of this project. Arduino IDE and MIT apps are used as a software that generates the codes to control overall programmes and build the interface for users to interact. After the testing was conducted, all of the components and software have reacted as intended which produces the desired result which is the desired court’s line with selected choice. The multiple line that is produced in a surface has proven that the Design of Interactive Court Lines for Sports using LED’s project is useful and efficient to be used by the target group. In future, this project can be used by people to play different sports in a hall so that it is not wasting the spaces. This project will add new features as for the improvement so that it will be more efficient and innovative that could help to ease and encourage people in doing sports.